Modelling self-assessed vulnerability to HIV and its associated factors in a HIV-burdened country (2017)
Background: Globally, individuals’ self-assessment of vulnerability to HIV infection is important to maintain safer sexual behaviour and reduce risky behaviours. However, determinants of self-perceived risk of HIV infection are not well documented and differ. We assessed the level of self-perceived vulnerability to HIV infection in Nigeria and also identified its risk factors. Methods: We explored a recent nationally representative data with self-reported vulnerability (‘high’, ‘low’ and ‘no risk at all’) to HIV infection as the outcome of interest. Data were weighted and association between the outcomes and the risk factors determined. We used simple ordered logit regression to model relationship between the outcome variable and risk factors, and controlled for the significant variables in multiple ordered logistic regression at 5% significance level. Results: About 74% had good knowledge of HIV transmission and 6% had experienced STI recently. The likelihood of assessing oneself as having ‘no risk at all’ was 50% and for ‘high chances’ was 1.6%. Self-perceived high risk of HIV was higher among those who recently experienced STI (5.6%) than those who did not (1.7%), and also higher among those who recently engaged in transactional sex and had multiple sexual partners. The odds of good knowledge of HIV transmission on high self-perceived vulnerability to HIV was 19% higher than poor knowledge (OR ¼ 1.19, 95% CI: 1.12–1.27). Also, respondents who recently had multiple sexual partners were 72% (OR ¼ 1.72, 95% CI: 1.60–1.86) more likely to report self as having high risk. Younger respondents aged 14–19 years had higher odds of 41% (OR ¼ 1.41, 95% CI: 1.29–1.55) to perceive self as having high vulnerability to HIV than older respondents. Conclusion: High vulnerability to HIV infection was reported among younger respondents, those with history of STIS and those who engage in multiple sexual relations. Despite high level of risky sexual behaviour and good knowledge of HIV transmission and prevention found in this study, self-perceived vulnerability to HIV generally is low. For the low perception found in this study to translate to low chance of HIV infection, there is need for all stakeholders to embark on risk reduction initiatives through sexual education that would minimise risky sexual practices and ensuring availability and affordability of HIV prevention methods.